Coordination in functional traits of Populus euphratica leaves under salt stress - Li, Duan; Si, Jianhua; Ren, Xiaozong; Li, Jiyan (Frontiers in Forests and Global Change, 2023)
Leaf functional traits allow plant survival and maintain their ecosystem function. Salinity affects leaf functional traits, but coordination among leaf functional traits is poorly known and may depend on salt severity. To increase our understanding of the coordination of leaf functional traits under salt stress, we determined hydraulic, gas exchange, and physiological and biochemical parameters in Populus euphratica Oliv. (P. euphratica) grown under salinity treatments, as well as gas exchange parameters under different CO2 concentrations. We found that P. euphratica can reinforce its hydraulic capacity by increasing the water transfer efficiency of both its leaves and stems when a salinity threat occurs for a specific duration of stress. Its stems were more adaptable than leaves. The economic and hydraulic traits of P. euphratica leaves were consistent during the middle stages of salt stress, but inconsistent during the onset and late stages of salt stress. There was almost no biochemical limitation under severe salinity conditions, and CO2 enrichment of P. euphratica had a greater effect on leaf economic traits. The mechanism of toxic ion exclusion based on water availability and intracellular mechanisms in leaves contributed to salt tolerance when P. euphratica was exposed to salinity stress. There was also a coordination mechanism for the plants during increasing salt stress. The leaf intracellular traits of P. euphratica can coordinate with the leaf economic and hydraulic traits and form a defense mechanism to reduce salt damage and guarantee growth under saline conditions. In conclusion, P. euphratica, the main constructional species of riparian forests, adapts to saline environments by adjustment and coordination of leaf functional traits, ensuring survival. These results provide a scientific basis for riparian forest restoration.